Assessment of an Average Controller for a DC/DC Converter via Either a PWM or a Sigma-Delta-Modulator - R. Silva-Ortigoza; F. Carrizosa-Corral; J. J. Gálvez-Gamboa; M. Marcelino-Aranda; D. Muñoz-Carrillo; H. Taud (Abstract and Applied Analysis)
Sliding mode control is a discontinuous control technique that is, by its nature, appropriate for controlling variable structure systems, such as the switch regulated systems employed in power electronics. However, when designing control laws based on the average models of these systems a modulator is necessary for their experimental implementation. Among the most widely used modulators in power electronics are the pulse width modulation (PWM) and, more recently, the sigma-delta-modulator (Σ-Δ-modulator). Based on the importance of achieving an appropriate implementation of average control laws and the relevance of the trajectory tracking task in DC/DC power converters, for the first time, this research presents the assessment of the experimental results obtained when one of these controllers is implemented through either a PWM or a Σ-Δ-modulator to perform such a task. A comparative assessment based on the integral square error (ISE) index shows that, at frequencies with similar efficiency, the Σ-Δ-modulator provides a better tracking performance for the DC/DC Buck converter. In this paper, an average control based on differential flatness was used to perform the experiments. It is worth mentioning that a different trajectory tracking controller could have been selected for this research.